Endurance Exercise Enhances Emotional Valence and Emotion Regulation - Giles, Grace E.; Eddy, Marianna D.; Brunyé, Tad T.; Urry, Heather L.; Graber, Harry L.; Barbour, Randall L.; Mahoney, Caroline R.; Taylor, Holly A.; Kanarek, Robin B. (Frontiers in Human Neuroscience, 2018)
Acute exercise consistently benefits both emotion and cognition, particularly cognitive control. We evaluated acute endurance exercise influences on emotion, domain-general cognitive control, and the cognitive control of emotion, specifically cognitive reappraisal. Thirty-six endurance runners, defined as running at least 30 miles per week with one weekly run of at least 9 miles (21 female, age 18-30 years) participated. In a repeated measures design, participants walked at 57% age-adjusted maximum heart rate (HRmax) (range 51-63%) and ran at 70% HRmax (range 64-76%) for 90 minutes on two separate days. Participants completed measures of emotional state and the Stroop test of domain-general cognitive control before, every 30 minutes during, and 30 minutes after exercise. Participants also completed a cognitive reappraisal task after exercise. Functional near-infrared spectroscopy tracked changes in oxygenated and deoxygenated hemoglobin levels in the prefrontal cortex (PFC). Endurance exercise elevated positive emotion and cognitive reappraisal success. Endurance exercise reduced Stroop response time and test-evoked PFC oxygenation during exercise. Results suggest that even at relatively moderate intensities, endurance athletes benefit emotionally from running both during and after exercise, and task-related prefrontal cortex oxygenation reductions do not appear to hinder prefrontal-dependent cognitive control.